2014
DOI: 10.1210/jc.2013-3618
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Molecular Characterization of Patients With Dyshormonogenic Congenital Hypothyroidism Reveals Specific Diagnostic Clues for DUOX2 Defects

Abstract: The defects in the peroxide generation system are common among congenital hypothyroidism patients with PIOD. The most robust clinical parameters for selecting patients for DUOX2 analysis have been identified, and several DUOX2 variants have been functionally characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 25 publications
4
69
1
Order By: Relevance
“…In contrast, the in silico assays suggested that the three polymorphic variants -p.P138L, p.H678R, and p.L1067S -were silent polymorphisms. This was consistent with a previous expression study (25). Previous studies showed that p.H678R did not reduce H 2 O 2 production (14,34).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the in silico assays suggested that the three polymorphic variants -p.P138L, p.H678R, and p.L1067S -were silent polymorphisms. This was consistent with a previous expression study (25). Previous studies showed that p.H678R did not reduce H 2 O 2 production (14,34).…”
Section: Discussionsupporting
confidence: 93%
“…Other reports have shown that biallelic DUOX2 mutations cause mild to moderate CH (13,14,15,16,19,22,30). Recently, some studies have shown that DUOX2 defects are the predominant cause of CH associated with dyshormonogenesis (13,14,15,16,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with DUOX2 variants usually show borderline blood spot TSH levels at first neonatal screening and subsequently high serum TSH at confirmatory tests (TSH >100 mIU/L) with low FT4, higher thyroglobulin (Tg) levels, and hyperplastic thyroid gland at birth [47]. …”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
“…Disease-causing mutations are usually biallelic, with the exception of monoallelic DUOX2 , IYD, and TSHR mutations, which may also confer a phenotype (1). Phenotypic heterogeneity in cases harboring similar causative mutations suggests that mono- and polygenic factors and environmental modulators may also play a role in determining disease severity (7, 8). …”
mentioning
confidence: 99%